2018
DOI: 10.3389/feart.2018.00071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fjord Geometry on Grounding Line Stability

Abstract: Recent and past retreat of marine-terminating glaciers are broadly consistent with observed ocean warming, yet responses vary significantly within regions experiencing similar ocean conditions. We assess how fjord geometry modulates glacier response to a regional ocean warming on decadal to millennial time scales, by using an idealized, numerical model of fast-flowing glaciers including a crevasse-depth calving criterion. Our simulations show that, given identical climate forcing, grounding line responses can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 96 publications
2
25
0
Order By: Relevance
“…Tidewater glacier fjord geometry is known to play a role in stabilizing a retreating terminus, by providing a variety of pinning points—for example, constrictions, sills, and bends—which can impede frontal ablation by reducing the area exposed to melting, reduce calving rates by altering near‐terminus stresses, and allow the glacier time to thicken (Åkesson et al, 2018; Amundson & Carroll, 2018; Carr et al, 2014; Catania et al, 2018; Mercer, 1961; Post, 1975). McNabb and Hock (2014) applied the term “step change retreats” to tidewater glacier retreats where constrictions or other factors result in a stillstand of several years or more between periods of rapid retreat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tidewater glacier fjord geometry is known to play a role in stabilizing a retreating terminus, by providing a variety of pinning points—for example, constrictions, sills, and bends—which can impede frontal ablation by reducing the area exposed to melting, reduce calving rates by altering near‐terminus stresses, and allow the glacier time to thicken (Åkesson et al, 2018; Amundson & Carroll, 2018; Carr et al, 2014; Catania et al, 2018; Mercer, 1961; Post, 1975). McNabb and Hock (2014) applied the term “step change retreats” to tidewater glacier retreats where constrictions or other factors result in a stillstand of several years or more between periods of rapid retreat.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid retreat often follows-for example, several kilometers in a few years (McNabb & Hock, 2014)-until the terminus stalls in shallower water or at a constriction in the fjord (e.g., Åkesson et al, 2018;Amundson & Carroll, 2018;Catania et al, 2018;Mercer, 1961;Nolan et al, 1995;Post, 1975). Over time, positive mass balance in combination with MB growth can lead to glacier growth and readvance, potentially asynchronous with regional trends (e.g., Taku Glacier: Pelto et al, 2008;Post & Motyka, 1995;Hubbard Glacier: Barclay et al, 2001;Trabant et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enderlin et al () found that, all else equal, glaciers with wider termini and/or with geometries that widen inland of the terminus are more sensitive to climate perturbations than their narrower counterparts. In fact, inland widening of the fjord may exert stronger control over retreat than the presence or absence of a terminal moraine (Åkesson et al, ).…”
Section: Controls On Outlet Glacier Dynamicsmentioning
confidence: 99%
“…Fjords act as important repositories for glacial-marine sediments deposited by retreating glaciers because once a marineterminating glacier has its grounded margin within a fjord, any sediments expelled from it are often effectively trapped in the narrow basin setting. In addition, fjord geometry strongly influences glacier retreat behaviour because bathymetric sills, fjord constrictions and turns in the fjord planform shape all provide stability either by reducing the flux at the grounding line and/or by providing lateral buttressing (Warren and Hulton, 1990;Hill et al, 2018;Åkesson et al, 2018;Catania et al, 2018).…”
Section: Introductionmentioning
confidence: 99%